The Compensatory Tillering in the Forage Grass Hordeum brevisubulatum After Simulated Grazing of Different Severity - Yuan, Jihong; Li, Haiyan; Yang, Yunfei (Frontiers in Plant Science, 2020)
The response of compensatory growth is an important adaptive strategy for plants to herbivore foraging. However, most previous researches on plants compensatory growth focused on the compensation of the biomass or the number of sexual reproductive offspring, neglected the compensatory growth of vegetative reproduction. It is important not only for plants compensatory growth studies, but also for theoretical and practical of grassland production. The clonal tussock grass, Hordeum brevisubulatum was selected as research object. Four different clipping intensities (unclipping and clipping stubble at 15cm, 10cm and 5cm height) at jointing stage and flowering stage were implemented to study the effect of simulated foraging. To explore the effect of recovery growth time on plant growth after simulated foraging, three times sampling were taken at different recovery time after simulated foraging (respectively 1, 3 and 7 weeks). We found light and moderate simulated foraging intensity significantly increased the number of buds and juvenile ramets, the promotion of simulated foraging on the number of buds and juvenile ramets was higher in jointing stage than flowering stage, and the increase of simulated foraging intensity decreased with the prolong of recovery growth time. The number of ramets signifcantly decreased with the increase of simulated foraging in both jointing stage and flowering stages at 1week after foraging, and the decreasing effect weakened with the prolong of recovery growth time. The buds number mainly showed over-compensation, the juvenile ramets number showed complete compensation, while the ramets number showed under-compensation at 1 week and 3 weeks after recovery growth. The number of ramets showed complete compesation under different foraging intensities in jointing stage, while showed under-compensation in flowering satge at 7 weeks after recovery growth. Our results indcated that different foraging intensities in jointing stage could promote the output of ramets with matter production capacity from buds and juvenile ramets, then improve the ability of compensatory growth. Therefore, in the plants production, there will be no harmful effect on the renewal and productivity of H. brevisubulatum population to graze with different foraging intensities in jointing stage.